The Impact of Technology and Social Media on Marriage and Divorce: A Study in Besilam Village, Langkat Regency - Sendy, Beby; Rossanty, Yossie; Hawawari, Muhammad Fadhiil (PT FORMOSA CENDEKIA GLOBAL, 2024)
In today's rapidly evolving digital era, technology and social media have become integral parts of daily life. From connecting people worldwide to shaping how we communicate, work, and play, these advancements have profoundly transformed social, cultural, and economic dynamics. This article explores the significant role of technology and social media in the modern world and examines their influence on how we live, interact, and share information. While social media serves as an effective two-way communication tool, its impact can vary depending on how it is used. The concept of communication and information-sharing via computer networks, which predates modern social media, marked the foundation for what we now recognize as social media platforms. As technology and social media continue to advance, they have given rise to new societal phenomena, including divorces stemming from relationships formed through social media interactions. Remarkably, marriage ceremonies can now be conducted via video calls, and divorces can be finalized through video conferences. The ongoing development of technology has significantly broadened societal knowledge. The emergence of diverse social media platforms has further enabled people to expand their social networks and forge new friendships.